If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 10) = (86 + x) Reorder the terms: (10 + 2x) = (86 + x) Remove parenthesis around (10 + 2x) 10 + 2x = (86 + x) Remove parenthesis around (86 + x) 10 + 2x = 86 + x Solving 10 + 2x = 86 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 10 + 2x + -1x = 86 + x + -1x Combine like terms: 2x + -1x = 1x 10 + 1x = 86 + x + -1x Combine like terms: x + -1x = 0 10 + 1x = 86 + 0 10 + 1x = 86 Add '-10' to each side of the equation. 10 + -10 + 1x = 86 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 86 + -10 1x = 86 + -10 Combine like terms: 86 + -10 = 76 1x = 76 Divide each side by '1'. x = 76 Simplifying x = 76
| 81=.5(9)h | | 76+x=180 | | X+7X-6=20 | | F(x)=-2x+2 | | 7(5w+8)=21 | | 2(3d+1)=-52 | | 4(-1+3d)=92 | | 5(4x+10)=190 | | 4(5+5t)=60 | | 2(3b-8)=14 | | 5k^2-34k-7=0 | | 8n+2=17 | | 2(4+5w)=98 | | 20-x/3=x/10 | | 5k^2-34k-7=o | | 2(1-2k)=-10 | | 7(4x+2)=350 | | 3(10+4b)=66 | | 3w+=2 | | 7(1k-10)=-7 | | 0.1=15x+0.56x^2 | | 3(5t-8)=141 | | 18=.5h(6+1.2) | | y=-4(x+2)2-3 | | 7(5m+8)=161 | | 2(4t+1)=42 | | 4(-1+1a)=-44 | | 6(5m+8)=78 | | 6(-2+7a)=-54 | | 2p+5=2 | | 3/4+1/3t=2/4 | | 4(4+w)=-4 |